DESAIN MOTIF MOZAIK PADA REGULER DECAGON BERBASIS GOLDEN TRIANGLE - Rosyadi, Itaniza; Kusno, K; Santoso, Kiswara Agung (KadikmA, 2012)
Abstract. Decagonal Penrose Mosaic is a decagonal interior design constructed by applying the basic of golden triangle Penrose tile. There are several techniques to design the mosaic, some of them are as follows: (1) constructing Penrose tile on the fifth iterations constructed from isosceles triangles which on each triangle is defined by decagon sector; (2) stating Penrose symmetry base as the mosaic design base; (3) dividing each Penrose tile golden triangle into 3 zone; (4) stating Penrose symmetry base to fill in Penrose tile golden triangle in each zone; (5) coloring the interior Penrose symmetry base and the backgrounds. The formed design has been found several Penrose mosaic models in full symmetry, not fully symmetry, similar and overlap, which each models has natural motive and symmetry characteristics. By using the different coloring techniques it has been formed some coloring pattern on the centre, homogenous distribution, or spreading. This would enrich the varieties of mosaic design forms. Key Words : decagonal golden triangle Penrose tile, Penrose mosaic